DEXAMETHASONE INTRAVITREAL IMPLANT FOR THE TREATMENT OF RECALCITRANT MACULAR EDEMA AFTER RHEGMATOGENOUS RETINAL DETACHMENT REPAIR. Issue 6 (June 2018) - Thanos, Aristomenis; Todorich, Bozho; Yonekawa, Yoshihiro; Papakostas, Thanos D.; Khundkar, Tahsin; Eliott, Dean; Dass, Ashvani B.; Williams, George A.; Capone, Antonio; Faia, Lisa J.; Wolfe, Jeremy D.; Hassan, Tarek S.; et al.
Abstract : Purpose: To investigate the efficacy of the intravitreal dexamethasone implant as the treatment for recalcitrant macular edema after successful rhegmatogenous retinal detachment repair. Methods: A retrospective review of the medical records was performed on 17 consecutive patients (17 eyes) with recalcitrant macular edema associated with rhegmatogenous retinal detachment repair who were treated with a single or multiple injections of an intravitreal dexamethasone 0.7-mg implant (Ozurdex; Allergan Inc) at two centers. Main outcomes of the study were change in logarithm of the minimum angle of resolution visual acuity, measurement of central foveal thickness, and macular cube volume as measured by spectral domain optical coherence tomography and frequency of complications. Results: The mean age was 67 years (range, 51–78 years). All 17 patients received previous topical therapy and 12 of them had previous administration of intravitreal triamcinolone with persistence of macular edema. Baseline mean best-corrected visual acuity was 20/100 (logarithm of the minimum angle of resolution 0.75; range, 0.18–1.3 ±0.37) in the affected eyes. There was a statistically significant improvement in best-corrected visual acuity at 1 month ( P < 0.001) and 3 months ( P = 0.01). Mean baseline central foveal thickness was 505 μm, and mean macular cube volume was 10.62 mm 3 . There was a statistically significant decrease in central foveal thickness and macular cube volume at 1 month (505–290 μ m, P = 0.013 and 10.62–9.13 mm 3, P < 0.0001) and 3 months ( P = 0.01). All patients developed recurrence of macular edema at 3 months, which required retreatment. The average number of implants was 4 (range, 1–14). No adverse effects such as retinal detachment or endophthalmitis occurred. Two patients experienced an increase in intraocular pressure that was controlled with topical therapy. Conclusion: Macular edema that occurs in eyes after successful repair of rhegmatogenous retinal detachment can be chronic and recalcitrant, and may be successfully and safely treated with the dexamethasone intravitreal implant. Abstract : Supplemental Digital Content is Available in the Text.The authors present a cohort of patients with recalcitrant cystoid macular edema after rhegmatogenous retinal detachment repair, which was successfully treated with dexamethasone intravitreal implant.